2016
DOI: 10.1155/2016/2856926
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab: Another Medication Related to Osteonecrosis of the Jaws?

Abstract: Objective. The acronym MRONJ has been created in order to identify “Medication-Related Osteonecrosis of the Jaw,” observed after the use of Bisphosphonates, RANK ligand inhibitor, and antiangiogenic medications. Only a case of osteonecrosis of the jaw in a Chron's disease patient following a course of Bisphosphonate and Adalimumab therapy has been recently described, so that it has been supposed that also this medication could promote manifestation of osteonecrosis. Clinical Case. On August, 2014, a 63-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 17 publications
1
50
0
1
Order By: Relevance
“…In the updated guidelines from the American Association of Oral and Maxillofacial Surgeons (AAOMS), the term “medication‐related osteonecrosis of the jaw (MRONJ)” was introduced in light of the large body of evidence linking ONJ to non‐BP drugs indicating that ONJ is no longer considered a class adverse effect of BPs. ONJ has been associated with other classes of drugs, including RANKL inhibitors, vascular endothelial growth factor (VEGF) inhibitors, as well as mammalian target of rapamycin (m‐TOR) inhibitors, and more recently, adalimumab (\an inhibitor for tumor necrosis factor α, TNF‐α) has also been found to be associated with ONJ …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the updated guidelines from the American Association of Oral and Maxillofacial Surgeons (AAOMS), the term “medication‐related osteonecrosis of the jaw (MRONJ)” was introduced in light of the large body of evidence linking ONJ to non‐BP drugs indicating that ONJ is no longer considered a class adverse effect of BPs. ONJ has been associated with other classes of drugs, including RANKL inhibitors, vascular endothelial growth factor (VEGF) inhibitors, as well as mammalian target of rapamycin (m‐TOR) inhibitors, and more recently, adalimumab (\an inhibitor for tumor necrosis factor α, TNF‐α) has also been found to be associated with ONJ …”
Section: Introductionmentioning
confidence: 99%
“…ONJ has been associated with other classes of drugs, including RANKL inhibitors, vascular endothelial growth factor (VEGF) inhibitors, as well as mammalian target of rapamycin (m-TOR) inhibitors, (5) and more recently, adalimumab (an inhibitor for tumor necrosis factor a, TNF-a) has also been found to be associated with ONJ. (6) Although more than a decade has passed since the first reported cases of ONJ, the pathophysiology of this disease remains elusive despite all ongoing efforts aimed at not only deciphering its pathogenesis but also identifying the patients at risk of developing ONJ when treated with relevant medications. The fact that ONJ develops in a minority of patients receiving the aforementioned drug classes suggests that genetics may contribute to or has a role in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…ONJ may be related to adalimumab and/or infliximab therapy, 2 anti TNF-α antibody used to treat Crohn's disease and other autoimmune diseases. Few authors reported a relationship between infliximab and/or adalimumab therapy and appearance of ONJ [2][3][4]. In this particular case the area of exposed bone didn't appear after a surgical odontostomatological procedure, but the patient showed a severe generalized periodontitis, a well known ONJ risk factor.…”
Section: Published: 11 December 2019mentioning
confidence: 77%
“…No. of patients Ciantar 2007 29 Case report 1 Cassoni 2016 30 Case report 1 Tsuchiya 2016 31 Case report 1 Aghaloo 2017 32 Case study 1* Favia 2017 33 Case report 1 Cillo 2019 34 Case report 1 * 6 patients but only 1 fitted the criteria for this review.…”
Section: Type Of Studymentioning
confidence: 99%